Analysis of Calculation of Income Tax (PPH) for 21 Permanent Employees: Analisis Perhitungan Pajak Penghasilan (PPH) 21 Pegawai Tetap - Aswijayanti, Putri; Dewi, Santi Rahma (Indonesian Journal of Innovation Studies, 2023)
This study aims to analyze the Calculation of Income Tax (PPH) for 21 Permanent Employees (Studies on Cv. Global Mulya Persada, Cv. Putri Jaya Persada, and Cv. Conscience). The method used in the quantitative approach. The research approach in this thesis uses a quantitative research approach with a descriptive approach. The object of this research is the Analysis of Income Tax Calculation (Pph) for 21 Permanent Employees (Studies on Cv. Global Mulya Persada, Cv. Putri Jaya Persada, and Cv. Conscience). With descriptive research, the researcher only intends to describe (describe) or explain the symptoms that are currently happening. The results of this study indicate that in the procedure for applying the calculation of Article 21 income tax to the income of permanent employees, there is a difference between the calculation of the Article 21 income tax payable according to CV. Global Mulya Persada with the number of calculations according to the Calculation of Income Tax Article 21 which refers to the Income Tax Law no. 36 of 2008. CV. Putri Jaya Persada still uses the old 2015 PTKP tariff. In fact, in 2016 there was a new PTKP as stipulated in the Minister of Finance regulation PMK-101/PMK.010/2016 which is valid until now. As a result, it can be seen that the amount of PPh 21 deposited by CV. Putri Jaya Persada experienced overpayment. CV. Putri Jaya Persada also does not impose fines on permanent employees who do not have an NPWP. In the application of the calculation of PPh Article 21 to the income of permanent employees, it can be seen that the total amount of PPh 21 deposited by CV. Conscience is still underpaid. This is because employee meal allowances are not included as an addition to gross income. Whereas according to the Taxation Law no. 36 of 2008, the meal allowance is one of the components to increase gross income.